Eine Antwort auf die «Krise der Medizin»? Die Moderne Konstitutionslehre im Krisendiskurs 1925 bis 1933 - Metzger, Nadine (Gesnerus, 2019)
Discussing the alleged «crisis of medicine» (ca. 1925–33) German physicians addressed the underlying mindset of medical theory and practice. Identified as «scientific crisis», they called the scientific epistemology of medicine into question. Since 1911 modern constitutional medicine had offered concepts potentially useful to overcome this «crisis». Besides similar topics the two discussions shared prominent voices, presenting their ideas for better medicine in both discourses. However, this paper shows the minor role constitutional medicine actually played in the «crisis» discussion. It was rarely put forward as a solution to the supposed «crisis» and is conspicuously often discovered in discussions of historical background. Far more often, concepts designed to overcome constitutional medicine are invoked as a potential crisis solution, first and foremost the so-called «constitutional therapy» fathered by Vienna gynaecologist Bernhard Aschner which evokes pre-modern humoral pathology.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Bernhard Aschner; Constitutional medicine; Crisis of medicine; Holism; Medical epistemology